Homesickness and socio-cultural adaptation towards perceived stress among international students of a public university in Sabah: an exploration study for social sustainability - Balan Rathakrishnan; Soon Singh Bikar Singh; Mohammad Rahim Kamaluddin; Mohd Fahmi Ghazali; Azizi Yahaya; Noor Hassline Mohamed; Anath Rau Krishnan (MDPI AG, 2021)
When adolescents go overseas to study, they have to face the challenge of adapting to local cultures, homesickness, and dealing with the stress. This study aimed to investigate the socio-cultural adaptation, homesickness, and perceived stress among international students in relation to social sustainability in a public university in Sabah, Malaysia. This research also related how international students manage both positive and negative impacts on their social life in university. The study included all international students in that university except Bruneian and Indonesian students. The sample group comprised 100 male and 100 female students. This study used four questionnaires: (i) Perceived Stress Scale, (ii) Homesickness Scale, (iii) Socio-cultural Adaptation Scale, and (iv) Revised Socio-cultural Adaptation Scale. The results indicated that the socio-cultural adaptation and perceived stress levels were significantly correlated, r (198) = 0.354, p < 0.05. The level of homesickness and perceived stress were also significantly correlated, r (198) = 0.314, p < 0.05. The outcome of this study can help overseas students lead better lives abroad, while the university can arrange relevant activities to help them better adapt to local cultures and perceive less stress. The present study underlined the importance of increasing socio-cultural adaptation and social sustainability and decreasing homesickness among international students studying at the public university in Sabah